The Significance of City Logos in Destination Recognisability - Walas, Bartłomiej (Studia Oeconomica Posnaniensia, 2014)
At a time of intense competition between cities as tourist destinations, brand building is increasingly seen as a distinguishing feature of uniqueness. An important role in this strategy is played by recognisability markers. A multitude of media messages means that the recipients ought to be able to recognize the promoted product or service as quickly as possible. One of the most important features contributing to recognisability is the logo of a destination, but there is an ongoing debate regarding the graphical forms, attractiveness and effectiveness of logos. While the literature on brand management comprehensively describes the functions and the principles behind the creation of graphical signs, there are not many studies into their recognisability. Hence, the author presents the findings of a survey analysing the logos of several Polish cities, seeking empirical evidence for their role in marketing communications, as described in the literature.